Location analysis of parcel locker network: effects of spatial characteristics on operational performance - Ma, Bohao (2024)
Parcel lockers are automated self-collection stations commonly used for e-commerce deliveries. It has emerged as a promising solution that overcomes the operational and sustainability challenges arising from Last-Mile Delivery. In collaboration with a major Singapore-based parcel locker operator and using their nationwide operational data, we study the implications of parcel locker's spatial accessibility on their operational performance, namely demands and users’ time-to-pickup. Instead of measuring spatial accessibility by straight-line distances, we extend the concept by incorporating a more comprehensive set of spatial factors with the adoption of the 5Ds walkability framework. The framework systematically depicts the interplay between spatial factors and individuals’ walking behaviors that are directly related to their parcel locker usage. Positive correlations between population size, street connectivity, availability of living amenities, and bus stops in proximity of parcel lockers versus the demands are observed. In a similar vein, significant correlations between availabilities of living amenities and transit facilities versus consumers’ time-to-pickup are noted. The findings support the positive contribution of trip comfort to parcel lockers’ demands, while also demonstrating the paradoxical effects of trip-chaining convenience, which boosts demand but delays the pickup process. The study contributes to the literature by establishing linkage between spatial measurements and operational performance of parcel lockers with real-life operational data, which complements prior research that primarily relies on survey data. Besides, the study is the first to characterize the time-to-pickup, a critical parameter for network design and delivery operations.